An Updated Evidence-Based Practice Review on Teaching Mathematics to Students With Moderate and Severe Developmental Disabilities. (June 2019) - Spooner, Fred; Root, Jenny R.; Saunders, Alicia F.; Browder, Diane M.
The purpose of this review was to examine the body of research on teaching mathematics to students with moderate and severe developmental disability that has been published since 2005, reflecting changes in both the academic expectations for this population and research and design standards in the evidence-based practice (EBP) era. We examined research on teaching mathematical skills for students with moderate and severe developmental disability from 2005–2016 and found 36 studies (33 single-case and three group-experimental studies), updating the Browder, Spooner, Ahlgrim-Delzell, Harris, and Wakeman analysis. Of the 36 studies included in the review, 22 single-case and three group-design studies received a rating of high or adequate quality using the National Technical Assistance Center on Transition (NTACT) indicator criteria. In addition to systematic instruction, instructional procedures of technology-aided instruction, graphic organizers, manipulatives, and explicit instruction were found to be EBPs in teaching mathematics to this population.